Sufficient hepatic artery flow compensates for poor portal vein flow after liver transplantation in patients with portal vein thrombosis. Issue 11 (20th October 2019) - Sasaki, Kazunari; McVey, John C.; Firl, Daniel J.; Andreatos, Nikolaos; Moro, Amika; Coromina Hernandez, Laia; Matsushima, Hajime; Teresa, Diago Uso; Fujiki, Masato; Aucejo, Federico N.; Quintini, Cristiano; Kwon, Choon‐Hyuck D.; et al.
Abstract: Objective: Portal vein thrombosis (PVT) does not preclude liver transplantation (LT), but poor portal vein (PV) flow after LT remains a predictor of poor outcomes. Given the physiologic tendency of the hepatic artery (HA) to compensate for low PV flow via vasodilation, we investigated whether adequate HA flow would have a favorable prognostic impact among patients with low PV flow following LT. Methods: This study included 163 patients with PVT who underwent LT between 2004 and 2015. PV and HA flow were categorized into quartiles, and their association with 1‐year graft survival (GS) and biliary complication rates was assessed. For both the HA and the PV, patients at the lowest two quartiles were categorized as having low flow and the remainder as having high flow. Results: The median MELD score was 22 and 1‐year GS was 87.3%. As expected, GS paralleled PV flow with patients at the lowest flow quartile faring the worst. In combination of PV and HA flows, high HA flow was associated with improved 1‐year GS among patients with low PV flow ( P  = .03). Similar findings were observed with respect to biliary complication rates. Conclusions: Sufficient HA flow may compensate for poor PV flow. Consequently, meticulous HA reconstruction may be central to achieving optimal outcomes in PVT cases.